2005
DOI: 10.1165/rcmb.2005-0039oc
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-Induced Endothelial Arginase Expression Is Dependent on Epidermal Growth Factor Receptor

Abstract: L-arginine is metabolized to nitric oxide (NO) by NO synthase (NOS), or to urea and L-ornithine by arginase. L-ornithine contributes to vascular remodeling in pulmonary hypertension via metabolism to polyamines and proline. Previously we found that cytokines upregulate both NOS and arginase in pulmonary arterial endothelial cells. We hypothesized that cytokine-induced arginase I and II expression depend on epidermal growth factor (EGF) receptor (EGFR) activity. Bovine pulmonary arterial endothelial cells were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 34 publications
2
60
0
Order By: Relevance
“…Consistent with this hypothesis, increased vascular arginase activity was reported to contribute to decreased endotheliumdependent NO production in pathologic conditions such as hypertension (19,20), atherosclerosis (21), diabetes (22), and erectile dysfunction (23), or in aging (24). Moreover, even though the regulating factors of arginase expression/activity remain largely unknown, it was demonstrated that various proinflammatory cytokines can act as inducers of arginase expression in cultured endothelial cells (18,25,26).…”
mentioning
confidence: 78%
“…Consistent with this hypothesis, increased vascular arginase activity was reported to contribute to decreased endotheliumdependent NO production in pathologic conditions such as hypertension (19,20), atherosclerosis (21), diabetes (22), and erectile dysfunction (23), or in aging (24). Moreover, even though the regulating factors of arginase expression/activity remain largely unknown, it was demonstrated that various proinflammatory cytokines can act as inducers of arginase expression in cultured endothelial cells (18,25,26).…”
mentioning
confidence: 78%
“…Higher levels and activity of the AII isoform have been detected in several of kinds of cancer in comparison to normal tissue. There is evidencethatsuggestsapossiblerelationshipbetweenreceptors such as the epidermal growth factor receptor (EGFR) andarginaseup-regulation [13].Interestingly,EGFRandestrogenalsohavebeenlinkedtothetranscriptionalregulation ofL-ornithinedecarboxylase(ODC) [14,15],anenzymethat metabolizes ornithine formed by AII to produce putrescine whichisessentialforcellularproliferationanddifferentiation [16]. In this study, we investigated the arginase activity in womenwithbreastcanceranddetermineditsassociationwith diseasestageandpresenceoftheestrogenreceptor(ER).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, arginase II is a mitochondrial protein that is not expressed in the liver (8). Both arginase isoforms are expressed in the lung (27). The metabolism of L-arginine by arginase results in the production of L-ornithine and urea.…”
mentioning
confidence: 99%